Un objet diplomatique : l’occupation industrielle des fonds marins à travers l’analyse des décisions politiques - Natália Frozel Barros (VertigO)
This article analyzes the first controversies and the decision-making process (1982-1989) that triggered the way in which seabed’s mineral exploitation zones are distributed today among countries. It starts with Reagan’s administration refusal to sign the United Nations Convention on the Law of the Sea. It then analyzes how UN legal framework is institutionalized albeit this posture. It hypothesizes that unofficial diplomatic and private-sector negotiations produce lock-in effects, which consolidate a path dependence towards the UN framework. The article draws from United Nations field research and from the institution’s archival records.